Gladiolus tenuis Bieb. у нижній частині долини річки Сейм - Rak, A.A.; Kozyr, M.S. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Modern spreading of Gladiolus tenuis Bieb. at the lower part of the valley of the river Seim was determined and ecologo-coenotical peculiarities of its habitat were studied, age and spatial structure of the population of the given species were investigated. The measures of Gladiolus tenuis conservation at the given region are proposed.